David Avidan’s Message from the Future. Nuclear fantasies of the galactic poet - Pietrzak, Maciej (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
David Avidan’s Message from the Future (1981) is one of few Israeli science fiction films ever made. This ambitious project of the well-known avant-garde poet has been forgotten for many years, as a result of a financial and artistic failure of the movie. The paper shows Avidan’s doomed film as an interesting cultural text that can be read as the director’s commentary on the Israeli reality of his time. Contrary to the artist’s claims about the global ambitions of the picture, Message from the Future is immersed in the local, exploring it under the guise of narrative structures borrowed from Hollywood. The text analyzes a precise deconstruction of the plot patterns characteristic for the classic American SF films from the 1950s, which Avidan adjusted to the Israeli sociopolitical landscape at the turn of the seventies and eighties.